An Evaluation of a Pipeline Program to Support Diversity in the Public Health Workforce: CDC Undergraduate Public Health Scholars (CUPS) Program. (December 2021) - Young, Kai Hsiang; Liburd, Leandris; Penman-Aguilar, Ana
Established by the Centers for Disease Control and Prevention (CDC), the goal of the CDC Undergraduate Public Health Scholars (CUPS) program is to expose students underrepresented in public health and medicine to careers in public health; ultimately, increasing the membership of these groups in these fields including biomedical sciences. CDC implemented a retrospective outcome evaluation of 1, 047 students who participated in the program from 2012 to 2017. Seventy-four percent (775) of students responded to the survey that captures their academic attainment and employment status, as well as their perception of the program's and mentors' influence on their career path. As of 2020, 639 (83.4%) of 775 participants have enrolled in an advanced degree program, with over 80% of 639 participants pursuing degrees in biomedical sciences, public health, or health care (BSPHHC)–related fields. Two thirds (374/566) of participants who reported they had ever been employed in a career position are working/have worked in BSPHHC-related fields. Overall, 77.4% (600) of 775 participants reported either the program or the mentors, or both were extremely or very influential to their career path. Students claimed the CUPS program had "opened their eyes, " inspired their interest, cultivated their passion for the field of public health, and fueled their drive to find solutions to and in social determinants of health and contribute to health equity. The opportunity to gain work and research experience through internship placements in CUPS has "opened doors" to first jobs and advanced education and training opportunities for many students.